Exploring trauma-related beliefs in the recovery and psychological health among female survivors of sexual violence in Johannesburg - Matamela, Nyambeni (University of Pretoria, 2025)
Mini Dissertation (MA (Counselling Psychology))--University of Pretoria, 2024.